PENINGKATAN HASIL BELAJAR BIOLOGI PESERTA DIDIK MELALUI PENERAPAN MODEL KOOPERATIF TIPE INSIDE OUTSIDE CIRCLE (IOC)EL KOOPERATIF TIPE INSIDE OUTSIDE CIRCLE (IOC) - Sari, Nur Indah; Ainulia, Andi Dewi Rizka; Lakamau, Yosina; Ahmad, Fandi (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
This Classroom Action Research aims to improve the biology learning outcomes of class X students of SMA Nasional Makassar through the application of the Inside Outside Circle (IOC) learning model on the classification of living things. The subjects of this study were class X students totaling 36 students. Data collection techniques were carried out by observing learning and learning outcomes tests at the end of each cycle. Data on student learning outcomes were collected through learning outcomes tests and then analyzed descriptively. The results showed an increase in student learning outcomes in cycle I with 47.23% to 77.78% in cycle II. This achievement shows that the IOC model can improve the biology learning outcomes of class X students of SMA Nasional Makasar. The IOC model can facilitate students to actively move, interact, work together, and help students understand biological concepts through peer explanations